Biogas från gödsel och gräs i kombination med dikalvsproduktion : möjligheter och begränsningar - Andersson, Johan; Brunge, Kristin; Walla, Tobias (SLU/Dept. of Energy and Technology, 2017)
Sweden has great potential for biogas production from manure, residues and energy crops. The environmental benefits are substantial, as the biogas production system reduces emissions from manure pits. The produced biogas can then also do well by replacing environmentally harmful electricity production or fuels.